Off-Line Contouring of the Data from the Multibeam Sea Beam - Desnoes, Y. (The International Hydrographic Review, 2015)
The development of the Sea Beam processing system was undertaken in 1977. We now have available a complete system for off-line play-back of the Sea Beam data right up to precise isobath contouring along the ship’s track. The problem of combining the data from several profiles has not been tackled, but nevertheless a notable improvement has been made over the real-time output of the system. Although most of the algorithms do not deserve detailed description, it seems of interest to present the method used for contouring separately, endeavouring to show its advantages and disadvantages by concrete examples. We will then try to draw some conclusions which may be of help in furthering our programme. Finally, other applications are given which describe the processing system’s results without going into details about the algorithms used.